2020
DOI: 10.1007/s00170-020-06339-x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into tool dynamics adaptation for chatter stability enhancement in the turning of flexible workpieces

Abstract: It seems a universally accepted doctrine that chatter resistance of a machining system can be improved with increasing stiffness of its components. However, the viewpoint that the tool stiffness reduction would be beneficial to cutting stability of flexible components has been demonstrated by the compliant tool-workpiece chatter model. This paper presents a comprehensive investigation of the dynamic interaction between the tool and the workpiece during turning operations and its effect on the cutting stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is concluded that the dominant vibration frequency as well as the energy distribution shifted with the transition of machining status during machining of Tube A, leaving distinct chatter marks on the machined surface. The physical mechanism behind these phenomena could be that the moving contact point between the cutting tool and the workpiece in operation leads to time-varying and position-dependent dynamics of the machining system, which critically determines the chatter stability of machining processes [24][25][26].…”
Section: B Chatter Feature Extractionmentioning
confidence: 99%
“…It is concluded that the dominant vibration frequency as well as the energy distribution shifted with the transition of machining status during machining of Tube A, leaving distinct chatter marks on the machined surface. The physical mechanism behind these phenomena could be that the moving contact point between the cutting tool and the workpiece in operation leads to time-varying and position-dependent dynamics of the machining system, which critically determines the chatter stability of machining processes [24][25][26].…”
Section: B Chatter Feature Extractionmentioning
confidence: 99%